2021
DOI: 10.1002/pssb.202100140
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Single‐Phase High‐Entropy Nitrides from First‐Principles Calculations

Abstract: Entropy‐forming ability (EFA) is used as a descriptor to identify possible single‐phase high‐entropy nitrides (HENs) from eight cation candidates Al, Si, Ti, V, Cr, Zr, Nb, and Mo. Around 56 five‐cation HEN compositions using density functional theory calculations of 2744 ten‐atom supercells are evaluated. Ten HEN compositions with high EFA values are identified, and among them AlCrNbTiVN5 has the highest EFA value. Cation‐nitrogen bond length statistics shows that HENs with small lattice distortion tend to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Such distortion affects the material's propensity to form a stable single-phase structure, as a uniform distribution of atoms is generally favored for higher EFA values. Our findings align with those of an existing study [32], which also reported that the incorporation of Si led to a compacting of the crystal lattice and consequently, a reduction in the EFA.…”
Section: Applications Of Sisso Model For New Hen Ceramicssupporting
confidence: 93%
See 2 more Smart Citations
“…Such distortion affects the material's propensity to form a stable single-phase structure, as a uniform distribution of atoms is generally favored for higher EFA values. Our findings align with those of an existing study [32], which also reported that the incorporation of Si led to a compacting of the crystal lattice and consequently, a reduction in the EFA.…”
Section: Applications Of Sisso Model For New Hen Ceramicssupporting
confidence: 93%
“…For the initial prediction phase, we compiled a dataset of 56 samples, each with its corresponding EFA value as the target property. These EFA values were sourced from the theoretical computational data based on bulk HEN ceramic materials featuring facecentered cubic structures [32]. The EFA values are shown in Table A1.…”
Section: Data Collection and Integrationmentioning
confidence: 99%
See 1 more Smart Citation